The Wiley‐Blackwell Handbook of Family Psychology 2009
DOI: 10.1002/9781444310238.ch40
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, and Bisexual Family Psychology: A Systemic, Life‐Cycle Perspective

Abstract: A systemic approach recognizes that individuals are influenced by their families, friends, communities, and workplaces, as well as broader societal institutions and ideologies (Whitechurch & Constantine, 1993; see Chapter 1, this volume). Individuals exist within, are shaped by, and interact with multiple intersecting contexts. Further, these interactions necessarily shift throughout the life cycle as individuals develop, form relationships, and create their own families and communities. A systemic approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…), including LG adoptive parent families (Lamb, 2012;Farr, 2017). Even so, in the US, adoptive parents often face stigma (e.g., concerns about parenting ability; Miall, 1987) related to "non-traditional" family structures (i.e., differing from married heterosexual parents with biologically related children), and LG adoptive parents often face additional stigma based on sexual identity (Goldberg, 2009;Herek, 2010;Goldberg and Smith, 2014;Lo et al, 2019). For example, the question of whether samegender couples could raise children as effectively as do differentgender couples was a central debate in the ruling for marriage equality in the US, a ruling that held important legal implications about whether (married) same-gender couples could jointly adopt children (American Psychological Association [APA], 2015;Obergefell v. Hodges, 135 S. Ct. 2584, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…), including LG adoptive parent families (Lamb, 2012;Farr, 2017). Even so, in the US, adoptive parents often face stigma (e.g., concerns about parenting ability; Miall, 1987) related to "non-traditional" family structures (i.e., differing from married heterosexual parents with biologically related children), and LG adoptive parents often face additional stigma based on sexual identity (Goldberg, 2009;Herek, 2010;Goldberg and Smith, 2014;Lo et al, 2019). For example, the question of whether samegender couples could raise children as effectively as do differentgender couples was a central debate in the ruling for marriage equality in the US, a ruling that held important legal implications about whether (married) same-gender couples could jointly adopt children (American Psychological Association [APA], 2015;Obergefell v. Hodges, 135 S. Ct. 2584, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic epistemology of CFP may facilitate an exploration of diversity issues because systems theory avoids the extreme individualism of Western ideology and recognizes dynamic processes and systemic functioning in social relations (Patterson & Sexton, 2013). Students need to be exposed to the extensive CFP literature on various aspects of diversity, including ethnicity, culture, gender, sexual identity, physical ability, religion, and socioeconomic status (Boyd-Franklin & Karger, 2012;Falicov, 2012Falicov, , 2013Goldberg, 2009;McGoldrick, Giordano, & Garcia-Preto, 2005), as well as to critiques of Eurocentric assumptions or foci and to alternative CFP models that pay attention to differences in worldviews or values, power dynamics, context of experience, and perceived distance (Kelly, Bhagwat, Maynigo, & Moses, 2014). Entry-level skill development may focus on individual and cultural differences in the establishment of the therapeutic alliance, culturally centered assessment, selection of culturally appropriate interventions, and inculcation of a culturally centered perspective that recognizes the need for continued openness to personal development in multiculturalism (Stanton & Welsh, 2011).…”
Section: Diversity Competencymentioning
confidence: 99%
“…Goldberg (2009) argued that “turning to child outcomes, children of LGB parents do not appear to differ from children of heterosexual parents in terms of self-esteem, depression, behavioral problems, or social functioning” (p. 583). Riggs, McLaren, and Mayes (2009) concluded that “Studies have found that there may well be benefits for children raised in lesbian- or gay parent households …” (p. 52).…”
Section: Part 2: General Outcomes For Children Of Same-sex Parentsmentioning
confidence: 99%
“…(2003, p. 30) reported that at least one son of a single lesbian mother had a very atypically feminine score that had, apparently as an outlier, reduced the overall score on the Pre-School Activities Inventory (PSAI) gender role average for single lesbian mothers, a result that seems more like gender identity confusion, if not reversal, than gender flexibility, as labeled by Biblarz and Stacey (2010). Kuvalanka and Goldberg (2009) studied a subset of 18 LGBT children from among 78 adult children from LGBT families, all of whom had lesbian parents; of these, 4 were gender-queer (3) or gender ambiguous (1), quite possibly an indication of gender identity confusion or ambiguity.…”
Section: Looking Deeper Into the Researchmentioning
confidence: 99%
See 1 more Smart Citation